Brimstone [compact disc, unabridged] - Preston, Douglas J. (Preston, Douglas J. Pendergast novel., 2011)
Behind the gates of a Hampton estate, FBI Special Agent Pendergast discovers the carnage of a gruesome crime. The smoldering remains of an infamous art critic, a melted cross branding his chest, are found in a locked, barricaded attic. The hoofprint singed into the floorboards and the smell of brimstone recall the legendary horror of those who make a pact with the devil.